Retinoid X Receptor Agonists Upregulate Genes Responsible for the Biosynthesis of All-Trans-Retinoic Acid in Human Epidermis - Wu, Lizhi; Chaudhary, Sandeep C.; Atigadda, Venkatram R.; Belyaeva, Olga V.; Harville, Steven R.; Elmets, Craig A.; Muccio, Donald D.; Athar, Mohammad; Kedishvili, Natalia Y. (PLOS ONE, 2016)
UAB30 is an RXR selective agonist that has been shown to have potential cancer chemopreventive properties. Due to high efficacy and low toxicity, it is currently being evaluated in human Phase I clinical trials by the National Cancer Institute. While UAB30 shows promise as a low toxicity chemopreventive drug, the mechanism of its action is not well understood. In this study, we investigated the effects of UAB30 on gene expression in human organotypic skin raft cultures and mouse epidermis. The results of this study indicate that treatment with UAB30 results in upregulation of genes responsible for the uptake and metabolism of all-trans-retinol to all-trans-retinoic acid (ATRA), the natural agonist of RAR nuclear receptors. Consistent with the increased expression of these genes, the steady-state levels of ATRA are elevated in human skin rafts. In ultraviolet B (UVB) irradiated mouse skin, the expression of ATRA target genes is found to be reduced. A reduced expression of ATRA sensitive genes is also observed in epidermis of mouse models of UVB-induced squamous cell carcinoma and basal cell carcinomas. However, treatment of mouse skin with UAB30 prior to UVB irradiation prevents the UVB-induced decrease in expression of some of the ATRA-responsive genes. Considering its positive effects on ATRA signaling in the epidermis and its low toxicity, UAB30 could be used as a chemoprophylactic agent in the treatment of non-melanoma skin cancer, particularly in organ transplant recipients and other high risk populations.